2021
DOI: 10.2196/23328
|View full text |Cite
|
Sign up to set email alerts
|

Realistic High-Resolution Body Computed Tomography Image Synthesis by Using Progressive Growing Generative Adversarial Network: Visual Turing Test

Abstract: Background Generative adversarial network (GAN)–based synthetic images can be viable solutions to current supervised deep learning challenges. However, generating highly realistic images is a prerequisite for these approaches. Objective The aim of this study was to investigate and validate the unsupervised synthesis of highly realistic body computed tomography (CT) images by using a progressive growing GAN (PGGAN) trained to learn the probability distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…GAN is a learning technique that has recently been a focus of deep learning using AI, which is used to generate or transform images using adversarial generative neural networks to create artificial but realistic-looking images [ 6 , 15 ]. While conventional CNN models have utilized a method to train one multilayer artificial neural network, GAN differs in progressing learning by the interaction of two artificial neural networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GAN is a learning technique that has recently been a focus of deep learning using AI, which is used to generate or transform images using adversarial generative neural networks to create artificial but realistic-looking images [ 6 , 15 ]. While conventional CNN models have utilized a method to train one multilayer artificial neural network, GAN differs in progressing learning by the interaction of two artificial neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that it was difficult for the expert physician to accurately distinguish between synthetic and true brain images. Synthetic high-resolution body CT images with progressive growing GAN (PGGAN) were also indistinguishable from real images in VTT [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fields of application range from classification [ 19 , 20 , 21 ] to prediction [ 22 , 23 ]. Furthermore, generative adversarial networks (GANs) have been used for efficient data augmentation and to solve data privacy concerns [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GANs can achieve stateof-the-art synthetic generation of remarkably realistic images using CNN in an unsupervised manner. The GANs have been successfully applied in many fields including medical analysis, satellite imagery, computational fluid dynamics, and precision agriculture (Goodfellow et al, 2014;Nie et al, 2018;Wu et al, 2020;Pang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%